Neutrophil CD64 index for rapid diagnosis of Pneumocystis jirovecii pneumonia in malignancy patients requiring mechanical ventilation: a retrospective analysis - Li, Xiaoming; Yi, Hongyu; Wu, Guixin; He, Aiting; Li, Rui; Long, Yi; Lin, Changhai; Jiang, Zhengying (Frontiers in Microbiology, 2026)
BackgroundPneumocystis jirovecii pneumonia (PJP) incidence and associated mortality have risen significantly in non-HIV immunocompromised patients, highlighting the urgent need for rapid, non-invasive diagnostics. Current methods face limitations including invasiveness, prolonged processing, or inadequate specificity. The neutrophil CD64 (nCD64) index emerges as a promising novel biomarker. Here, we conducted this study to evaluate the diagnostic performance of nCD64 index for PJP and further assess the predictive value of its longitudinal changes for 28-day mortality.MethodsThis retrospective cohort study (July 2022–March 2025) analyzed mechanically ventilated malignancy patients with unexplained diffuse pulmonary infiltrates at a tertiary intensive care unit (ICU). PJP diagnosis required predefined clinical, radiological, and bronchoalveolar lavage fluid metagenomic next-generation sequencing (BALF mNGS) criteria. The nCD64 index was measured via flow cytometry at ICU admission and serially after ≥3 days of anti-PJP therapy. Diagnostic performance for PJP and prognostic value for 28-day mortality were assessed.ResultsAmong 28 PJP and 38 non-PJP patients, nCD64 index was significantly higher in PJP (13.33 vs. 2.84, p < 0.001). Receiver operating characteristic (ROC) curve analysis showed an area under the curve (AUC) of 0.846 (95% CI: 0.736–0.932) for PJP diagnosis, with sensitivity 89.3% and specificity 71.1% at cutoff ≥7. Multivariate analysis confirmed nCD64 index as an independent PJP predictor (OR = 1.097, 95% CI: 1.026–1.173; p = 0.007). Post-therapy nCD64 index elevation predicted 28-day mortality with high sensitivity (81.8%) and specificity (86.7%).ConclusionThe nCD64 index functions as a dual-purpose biomarker for malignancy patients with respiratory failure requiring mechanical ventilation: it provides a rapid, non-invasive diagnostic tool for PJP and dynamically stratifies mortality risk. Moreover, dynamic tracking offers a real-time window into treatment response, guiding therapeutic decisions.